2017
DOI: 10.3847/1538-4357/836/1/115
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Presence of Multiple Photometric Components in Nearby Early-type Galaxies Using SDSS

Abstract: We investigate two-dimensional image decomposition of nearby, morphologically selected early-type galaxies (ETGs). We are motivated by recent observational evidence of significant size growth of quiescent galaxies and theoretical development advocating a two-phase formation scenario for ETGs. We find that a significant fraction of nearby ETGs show changes in isophotal shape that require multi-component models. The characteristic sizes of the inner and outer component are ∼ 3 and ∼ 15 kpc. The inner component l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 101 publications
1
33
0
1
Order By: Relevance
“…We will also investigate secondary trends with stellar populations and gradients therein (e.g., Greene et al 2015;Goddard et al 2017;Oh et al 2017), the spatial extent of the ionized gas, and the presence or absence of an extended stellar halo.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We will also investigate secondary trends with stellar populations and gradients therein (e.g., Greene et al 2015;Goddard et al 2017;Oh et al 2017), the spatial extent of the ionized gas, and the presence or absence of an extended stellar halo.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these outliers appear round visually, suggesting that they have poorly measured ò values. A related issue is that we utilize an effective ò value, but in general these massive galaxies grow more flattened at larger radius (e.g., Huang et al 2012;Oh et al 2017), which may contribute to the scatter. However, the majority of these galaxies are quite elongated and display low levels of rotation along their major axis, with a high central dispersion (see example maps in Appendix A).…”
Section: Out Versus òmentioning
confidence: 99%
See 1 more Smart Citation
“…Two-dimensional analyses have also found that the stellar distributions of massive ETGs are often better fit by multiple-component models (e.g. Huang et al 2013a;Oh et al 2017). Huang et al (2013b) further suggest a connection between the multi-component nature of massive galaxies and their two-phase assembly history.…”
Section: Introductionmentioning
confidence: 98%
“…There have been multiple observational attempts to test the two-phase formation scenario using galaxies at low redshift, by investigating surface brightness or mass density profiles (e.g., Huang et al 2013a,b;Oh et al 2017), optical colour gradients (e.g., La Barbera et al 2010Barbera et al , 2012, and stellar population gradients (e.g., Coccato et al 2010Coccato et al , 2011Greene et al 2015; Barbosa et al 2016). These observations are generally consistent with the two-phase formation scenario.…”
Section: Introductionmentioning
confidence: 99%